Answer:
D(1, 2) → D'(2, 7)
E(-3, -5) → E'(-10, 0)
F(4, -1) → F'(11, 4)
Step-by-step explanation:
D(1, 2) → D' ________
Translate image (3x - 1, y + 5)
(1, 2), x = 1 and y = 2
3x - 1 = 3(1) - 1 = 3 - 1 = 2
y + 5 = (2) + 5 = 7
E(-3, -5) → E' ________
(-3, -5), x = -3 and y = -5
3x - 1 = 3(-3) - 1 = -9 - 1 = -10
y + 5 = (-5) + 5 = 0
F(4, -1) → F' ________
(4, -1), x = 4 and y = -1
3x - 1 = 3(4) - 1 = 12 - 1 = 11
y + 5 = (-1) + 5 = 4
Answer:
the median is 43
Step-by-step explanation:
Answer:
-8n + 9
Step-by-step explanation:
Given that,
A = -3n + 2
B = 5n - 7
Before solving you have to know that,
( + ) × ( + ) = ( + )
( - ) × ( - ) = ( + )
( + ) × ( - ) = ( - )
Let us solve now.
A - B
-3n + 2 -(5n - 7)
-3n + 2 - 5n + 7
Combine like terms
-3n - 5n + 2 + 7
-8n + 9
Hope this helps you.
Let me know if you have any other questions :-)